The quasi-market of employment services in Italy - Francesco Pastore (Global Labor Organization (GLO), 2019)
This paper aims to study the shortcomings and merits of the first experiment of quasi-market in the provision of employment services: the Lombardy DUL (Dote Unica Lavoro). This system, which has inspired the 2015 national reform within the Jobs Act, has reactivated and revitalized the sector by providing important job opportunities to jobless workers. The system has the typical problems of quasi-markets in the provision of public services (lion's share of private organizations; cherry picking; gaming). However, different expedients are devised in the program to minimize these shortcomings. The empirical analysis suggest that such phenomena if existent are at a physiological level. Analysis of the determinants of completing successfully the program provides non-trivial results as to, among others, the role organizations of different ownership type and of services provided.
Keywords: H44; H52; H76; I38; J68; R23; 330; Public employment services; Quasi-markets; Cherry-picking; Gaming; Lombardy region; Jobs Act